The Psychology of Altruism: Insights from Evolutionary and Social Psychology - Khadka, Chetan (Namuna Academic Journal, 2025)
Altruism, a fundamental aspect of human behavior, has been extensively studied from both evolutionary and social-psychological perspectives. This article provides a comprehensive review of the concept of altruism, exploring its definitions, historical development, and significance in psychology. Evolutionary theories, including kin selection, reciprocal altruism, and inclusive fitness, offer explanations for altruistic behavior as an adaptive mechanism shaped by natural selection. In contrast, social psychological approaches highlight the influence of situational factors, social norms, and empathy on altruistic actions. The integration of these perspectives, along with insights from neuroscience and anthropology, provides a holistic understanding of altruism. Emerging trends in the field, such as the impact of digital environments and cross-cultural variations, are discussed, along with practical implications for society and policy. The review also addresses ongoing challenges and controversies, emphasizing the need for continued research. This article contributes to a deeper understanding of altruistic behavior and offers valuable insights for fostering a compassionate and supportive society.